From the mountains to the plains: impact of climate change on water resources in the Koshi River Basin - Bharati, Luna; Bhattarai, Utsav; Khadka, Ambika; Gurung, Pabitra; Neumann, L. E.; Penton, D. J.; Dhaubanjar, Sanita; Nepal, S. (International Water Management Institute, 2019)
The Koshi Basin, spread across China, Nepal and India, is perceived as having high potential for hydropower and irrigation development, both seen as ways to promote economic development in the region. This paper quantifies and assesses the past and projected future spatial and temporal water balances in the Koshi Basin. Results show that precipitation and net water yield are lowest in the transmountain region and the Tibetan plateau. The values are highest in the mountain region, followed by the hills and Indo-Gangetic Plains. Approximately 65% of average annual precipitation is converted to flows, indicating high water availability. Actual evapotranspiration is highest in the Indo-Gangetic Plains region due to the presence of irrigated agriculture and a few forested mountain watersheds. As most of the water from the mountain and hill regions eventually flows down to the plains, the mountain and hill regions in Nepal are important for maintaining agriculture in the plains in both Nepal and India. Results from the flow analyses indicate the high temporal variability of flows in the basin. The frequent occurrences of both high- and low-flow events demonstrate the existing vulnerability of the region to both floods and droughts, leading to a very risk-prone livelihood system. Climate change projections show an increasing trend in precipitation and net water yield for most of the basin, except the transmountain region. Therefore, it is important to consider the climate change impacts on water resources in future planning.